Сборка роторов барабанно-дискового типа методом двух пробных сборок с замером биений на призмах – типовые процессы и алгоритмы расчетов - Филимонихин, Г. Б.; Невдаха, А. Ю.; Філімоніхін, Г. Б.; Невдаха, А. Ю. (My University, 2012)
Розробляється технологія складання міжопорних роторів газотурбінних двигунів (ГТД) барабанно-дискового типу (БДТ) методом двох пробних складань з заміром биття на призмах та типові процеси, призначені для визначення характеристик пар і оптимального складання ротора. Створюються алгоритми розрахунків, що забезпечують: визначення і аналіз характеристик пар; разове і оптимальне складання ротора тощо. Оптимізуються відомі алгоритми розрахунків, що забезпечують складання консольних роторів з заміром биття на призмах. В середовищі швидкої розробки додатків Borland Delphi створена комп'ютерна програма, що забезпечує розрахунки при складанні роторів ГТД БДТ методом двох пробних складань з заміром биття, як на поворотному складальному стапелі, так і на призмах. Is developed the technology of assembling of intersupporting rotors of the gas turbine engines of drum-disk type by the method of two test assembling with the measurement of the beats on prisms. Are developed the model processes which intended on determination of descriptions of pairs of rotor and optimum assembling of rotor. Are created the algorithms of computations which providing: determination of descriptions of pairs of rotor at measuring of beating on prisms; analysis of descriptions of pairs; a single virtual assembly of the rotor; optimum assembling of rotor; prognosis of beats of control surfaces of links of rotor and etc The known algorithms of computations, providing assembling of cantilever rotors with measuring of beating on prisms, are optimized. Are developed the typical processes and algorithms of computations, setting for determination of descriptions of pairs, single virtual assembly of the rotor, optimum assembling of rotor. On results the work in the environment of rapid development of supplements Borland Delphi was created the connected module of subprograms and computer program, providing computations at assembling of rotors of gasturbine engines of drum-disk type by the method o ftwo trial assembling with measuring of beats, both on a turning assembling device, and on prisms.Technologies of assembling of rotors and computer program allow optimum to collect the cantilever and intersupporting rotors GTE DDT on manufacture, to conduct the calculable and model experiments on the study of efficiency of method of two test assembling.
Keywords: газотурбинній двигатель; ротор барабанно-дискового типа; сборка ротора; технология сборки